Patient-centered care for patients with depression or anxiety disorder: an integrative review - Pinho, Lara Guedes de (2021)
People have specific and unique individual and contextual characteristics, so healthcare should increasingly opt for person-centered care models. Thus, this review aimed to identify and synthesize the indicators for the care process of the person with depression and/or anxiety disorders, based on patient-centered care, going through the stages of diagnostic assessment and care planning, including intervention. An integrative literature review with research in seven scientific databases and a narrative analysis were carried out. Twenty articles were included, with indicators for diagnostic evaluation and care/intervention planning being extracted. Care planning focused on people with depression and/or anxiety disorder must be individualized, dynamic, flexible, andparticipatory. It must respond to the specific needs of the person, contemplating the identification of problems, the establishment of individual objectives, shared decision making, information and education, systematic feedback, and case management, and it should meet the patient’s preferences and satisfaction with care and involve the family and therapeutic management in care. The existence of comorbidities reinforces the importance of flexible and individualized care planning in order to respond to the specific health conditions of each person.